In vivo confocal microscopy and histopathology of the conjunctiva in trachomatous scarring and normal tissue: a systematic comparison. Issue 10 (6th August 2013) - Hu, Victor H; Holland, Martin J; Cree, Ian A; Pullin, James; Weiss, Helen A; Massae, Patrick; Makupa, William; Mabey, David C W; Bailey, Robin L; Burton, Matthew J; Luthert, Phil
Abstract : Aim: To compare in vivo confocal microscopy (IVCM) with the histopathological examination of tissue and cellular changes in normal and diseased conjunctiva. Methods: Participants underwent clinical examination and IVCM of the tarsal conjunctiva. A biopsy of the upper tarsal conjunctiva was collected and stained with tinctorial stains and by immunohistochemical staining for CD45 and CD83. Connective tissue scarring, inflammatory cell density and the presence of dendritiform cells were quantitatively assessed in a masked manner by both IVCM and histological assessments for comparative analysis. Results: Thirty-four participants with severe trachomatous conjunctival scarring and 33 participants with healthy conjunctiva were recruited. The IVCM connective tissue scarring score was strongly associated with the histological grading of scarring (p<0.001). There was limited evidence of an association between the IVCM inflammatory cell infiltrate and the histological inflammatory cell grade (p=0.05). We did not find any evidence to support the hypothesis that dendritiform cells seen with IVCM are mature, conventional dendritic cells. Conclusions: The results show that IVCM can be used to robustly quantitate connective tissue scarring and also has a role in measuring the inflammatory cell infiltrate. The discordance between IVCM dendritiform cells and immunohistochemical dendritic cells may be a result of study limitations or may be because these dendritiform structures represent another cell type, such as fibroblasts, rather than dendritic cells.